Secondary battery

The foam sheet structure in secondary batteries addresses cell expansion and contraction issues, improving safety and performance by absorbing expansion, managing heat, and preventing thermal runaway.

JP7601268B2Active Publication Date: 2024-12-17DIC CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023578460
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-02-04
Filing Date
2023-01-19
Publication Date
2024-12-17
Estimated Expiration
2043-01-19

AI Technical Summary

Technical Problem

Existing secondary batteries face issues with expansion and contraction due to battery cell deterioration over time, leading to performance degradation and safety risks such as thermal runaway, fire, and damage, particularly with increasing capacity and heat generation during high-speed charging or discharging.

Method used

Incorporating a foam sheet with adhesive layers and optional flame-blocking, heat-absorbing, or heat-storage properties between battery cells to absorb expansion and contraction, thereby preventing heat generation and ignition, and isolating cells to manage internal pressure.

Benefits of technology

The foam sheet structure effectively absorbs expansion and contraction, preventing battery deterioration, reducing the risk of thermal runaway, and enhancing safety by managing heat and pressure within the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601268000002
    Figure 0007601268000002
  • Figure 0007601268000003
    Figure 0007601268000003
  • Figure 0007601268000004
    Figure 0007601268000004
Patent Text Reader

Abstract

The present invention addresses the problem of providing a secondary battery having a structure that can absorb the expansion or contraction of battery cells constituting the second battery associated with deterioration over time. The present invention pertains to a secondary battery characterized by comprising two or more battery cells, a case accommodating the battery cells, and a foam sheet positioned on the inner surface of the case and / or a foam sheet positioned so as to isolate the adjacent battery cells.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a secondary battery. [Background technology]

[0002] In response to the miniaturization of personal computers, mobile phones, video cameras, etc., there is an increasing demand for smaller and lighter batteries, and high-performance secondary batteries are becoming widespread. For example, lithium-ion secondary batteries are also used as on-board power sources for electric vehicles or hybrid vehicles, and various performance improvements are being made. In recent years, secondary batteries have become higher in capacity, and a secondary battery (secondary battery module) has been disclosed in which a plurality of battery cells, each of which contains and seals each component of a lithium-ion secondary battery, such as a positive electrode material, a negative electrode material, a separator, and an electrolyte, are stacked to form a unit and connected in series or in parallel using a bus bar (see, for example, Patent Document 1). It is known that the battery cells constituting a secondary battery deteriorate over time, causing the internal pressure in the battery cell to increase and the battery cell case to expand. When the battery cell case expands, in a secondary battery in which multiple battery cells are stacked, the outer surface of the battery cell case bulges, causing a defect in which the external shape of the secondary battery module changes, and the performance of the secondary battery deteriorates.

[0003] In order to suppress expansion or contraction of battery cells, for example, a secondary battery has been proposed which has a frame-shaped structure that restrains the battery cell unit in the stacking direction, and which provides gaps between each corner of the end separator arranged at both ends of the battery cell unit in the stacking direction, which is provided in a direction facing the frame, and each corner of the frame facing each corner of the end separator (see Patent Document 2); a specific cell stack structure has been proposed which has a plate material, an expandable member, and a connecting member capable of creep deformation at one end in the stacking direction in which multiple battery cells are stacked (see Patent Document 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-161681 A [Patent Document 2] JP 2017-162810 A [Patent Document 3] JP 2021-111573 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the structure of Patent Document 2 still has room for improvement in terms of the assembly of the secondary battery depending on the rigidity of the frame, and the structure of Patent Document 3 requires special mechanisms such as expandable and contractible members and connecting members in the secondary battery case, and there are still issues with respect to manufacturing costs, etc. In addition, as the capacity of secondary batteries increases, the temperature of the secondary batteries increases due to heat generation during high-speed charging or high-output discharging, which not only causes deterioration of the secondary batteries but also creates the risk of fire or battery damage due to a sudden temperature rise or thermal runaway. Therefore, there is a need to develop methods to improve the safety of secondary batteries and suppress their deterioration. An object of the present invention is to provide a secondary battery having a structure capable of absorbing expansion and contraction caused by deterioration over time of battery cells constituting the secondary battery. Another object of the present invention is to provide a secondary battery having a structure capable of absorbing expansion and contraction caused by deterioration over time of battery cells and preventing deterioration of the secondary battery due to heat generation and fire or damage due to thermal runaway. [Means for solving the problem]

[0006] The present invention relates to the following (1) to (6). (1) A secondary battery comprising two or more battery cells, a case for housing the battery cells, and either or both of a foam sheet disposed on the inner surface of the case and a foam sheet disposed so as to isolate the adjacent battery cells. (2) The secondary battery according to (1), in which the foam sheet further has an adhesive layer on the outermost layers on both sides, and the battery cells are fixed by the adhesive layer. (3) The secondary battery according to (1) or (2), in which the foam sheet further has a flame-shielding layer. (4) The secondary battery according to any of (1) to (3), in which the foam sheet is a foam sheet containing at least one type of heat absorbing agent or heat storage material. (5) The secondary battery according to any of (1) to (4), in which each of the battery cells is covered with the foam sheet with the positive electrode terminal and the negative electrode terminal of each of the battery cells exposed. (6) The secondary battery according to any of (1) to (5), in which the foam sheet has a thickness of 100 to 20,000 μm. Effect of the Invention

[0007] According to the present invention, it is possible to provide a secondary battery having a structure capable of absorbing expansion and contraction caused by deterioration over time of the battery cells constituting the secondary battery. Also, according to the present invention, it is possible to provide a secondary battery having a structure capable of absorbing expansion and contraction caused by deterioration over time of the battery cells and preventing deterioration of the secondary battery due to heat generation and fire or damage due to thermal runaway. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a perspective view showing a first embodiment of a secondary battery of the present invention. [Diagram 2] FIG. 2 is a partially cutaway perspective view of a secondary battery according to a second embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view of an example of a foam sheet included in the secondary battery of the present invention. [Figure 4] FIG. 2 is a schematic cross-sectional view of an example of a foam sheet included in the secondary battery of the present invention. [Diagram 5] 1 shows stress-compression strain curves of sheets 1 to 6 obtained in Examples 1 to 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described in detail. In this specification, a numerical range indicated using "to" indicates a range including the numerical values ​​before and after "to" as the minimum and maximum values, respectively.

[0010] The secondary battery of the present invention comprises two or more battery cells, a case for housing the battery cells, and either or both of a foam sheet arranged on the inner surface of the case and a foam sheet arranged so as to isolate adjacent battery cells from each other. Here, when a foam sheet is disposed so as to separate adjacent battery cells, the foam sheet is preferably sandwiched between the battery cells.

[0011] The type of secondary battery is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors, etc. Among these, a lithium ion battery is a suitable application.

[0012] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, a secondary battery of the present invention will be described in detail based on preferred embodiments shown in the accompanying drawings. First Embodiment First, a first embodiment of the secondary battery of the present invention will be described. FIG. 1 is a perspective view showing a first embodiment of a secondary battery of the present invention.

[0013] A secondary battery 100 shown in FIG. 1 is, for example, a secondary battery mounted on a vehicle or the like, and has a plurality of battery cells 1 and a case 10 for housing the battery cells 1 therein. The battery cell 1 constituting the secondary battery can be, for example, a battery cell in which a battery element including at least a positive electrode material, a negative electrode material, a separator, a positive electrode terminal, and a negative electrode terminal, etc., is enclosed within an exterior material, such as a battery exterior film. The exterior material is formed, for example, by heat-sealing the sealant layers of the battery exterior film, and has a flange portion (a region where the sealant layers are in close contact with each other by heat sealing) on ​​the periphery. A positive electrode tab (positive electrode terminal) 29 and a negative electrode tab (negative electrode terminal) 39 connected to the positive electrode material and the negative electrode material, respectively, protrude from the flange portion to the outside, and as shown in FIG. 1, the positive electrode tab 29 and the negative electrode tab 39 are sealed by a sealant 5 in an exposed state.

[0014] The secondary battery 100 of this embodiment is configured by housing a plurality of such battery cells 1 in a case 10. The case can be made of, for example, aluminum, iron, or a metal material containing these, or a resin material such as polyphenylene sulfide. Forming the case from a resin material contributes to reducing the weight of the secondary battery and can also increase adhesion with the foam sheet. The case 10 is composed of a box-shaped member having a bottom and peripheral walls, and a lid (not shown) is attached to close the opening. The lid is provided with a positive electrode terminal for external connection which is collectively connected to the positive electrode tabs 29 and a negative electrode terminal for external connection which is collectively connected to the negative electrode tabs 39 when attached to the case 10.

[0015] A foam sheet 20 is disposed on the inner surface of the case 10, and a foam sheet 30 is also disposed, preferably sandwiched between the battery cells, so as to separate the adjacent battery cells. In the secondary battery of the present invention, the foam sheet is preferably disposed both on the inner surface of the case and between the battery cells. With this configuration, the expansion or contraction of the battery cells due to deterioration over time of the secondary battery can be absorbed by the cushioning properties of the foam sheet. In this specification, the cushioning properties of a seat do not necessarily mean that the seat has good flexibility, impact resistance, and recovery in a compression test, but in particular mean that the range of effective strain due to stress is wide and the compression rate is large, as calculated from the stress-compression strain curve obtained in a compression test of the seat. In the secondary battery of the present invention, a sheet other than a foam may be used as the sheet having a wide range of effective strain due to stress and a large compressibility calculated from a stress-compression strain curve obtained in a compression test, although a foam sheet is highly preferred as an embodiment that provides better cushioning properties. When the foam sheet is sandwiched between the battery cells, the thermal insulation properties of the foam sheet suppress the temperature effect between the battery cells, and the cushioning properties of the foam sheet act as a buffer for volume changes due to expansion of the battery cells, for example, absorbing expansion in the stacking thickness direction, and easing an increase in internal pressure of the secondary battery. Note that in the secondary battery of the present invention, the foam sheet may be sandwiched between all of the two or more battery cells, or may be sandwiched between some of the battery cells.

[0016] [Foam sheet] The foam sheet constituting the secondary battery of the present invention may be a sheet made of a resin foam, or may be a single-layer sheet further containing a resin as a matrix and a heat absorbing agent or heat storage material described later, or may be a laminate further including a pressure sensitive adhesive layer, a flame shielding layer, or any other layer of any other composition described later, in addition to the foam sheet layer. Hereinafter, unless otherwise specified, a single-layer sheet consisting of only a layer containing a resin will be referred to as a "foamed sheet".

[0017] When the foam sheet is disposed on the inner surface of the case that houses the battery cells, or when the foam sheet is disposed so as to isolate adjacent battery cells from each other, for example, an adhesive, fusion (ultrasonic fusion, high-frequency fusion, heat fusion), pressure-sensitive adhesive, etc. can be used. When the foam sheet is a laminate further having an adhesive layer on the outermost layers on both sides, it is possible to omit the further use of an adhesive or pressure-sensitive adhesive, particularly when sandwiching the foam sheet between the battery cells, which is advantageous from the viewpoint of workability. Furthermore, since the battery cells are fixed by the adhesive layer, it is possible to prevent the battery cells from shifting.

[0018] Furthermore, if the foam sheet is a foam sheet further having a flame-shielding layer, a foam sheet containing one or more types of heat-absorbing agents or heat-storage materials described below, or a foam sheet having a flame-shielding layer and containing one or more types of heat-absorbing agents or heat-storage materials, it can absorb expansion and contraction that accompanies deterioration of the battery cell over time and can prevent deterioration of the secondary battery due to heat generation and fire or damage due to thermal runaway. In other words, a secondary battery having a structure can be provided that suppresses sudden temperature increases in the secondary battery due to heat generation during high-speed charging or high-output discharging, internal short circuits, etc., minimizes damage such as deterioration of the secondary battery due to heat generation and fire or breakage due to thermal runaway, and absorbs and extinguishes heat from battery cells that have become abnormally hot, thereby preventing or delaying subsequent explosions in other battery cells.

[0019] <Resin> Materials for the foam sheet include thermoplastic resins, thermosetting resins and elastomeric resins. Examples of thermoplastic resins include polyolefin resins such as polypropylene resin, polyethylene resin, poly(1-butene) resin, polyisobutylene resin, and polypentene resin; polyester resins such as polyethylene terephthalate; and synthetic resins such as polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, acrylic resin, polyvinyl acetal resin, polyvinyl alcohol resin, ethylene-vinyl acetate copolymer (EVA) resin, polycarbonate resin, polyphenylene ether resin, polyamide resin, polyvinyl chloride resin (PVC), novolac resin, and polyurethane resin. Examples of the thermosetting resin include synthetic resins such as epoxy resin, urethane resin, phenol resin, urea resin, melamine resin, unsaturated polyester resin, and polyimide. Examples of the elastomer resin include acrylonitrile-butadiene rubber, ethylene-propylene-diene rubber (EPDM), ethylene-propylene rubber, natural rubber, polybutadiene rubber, polyisoprene rubber, polystyrene-polybutadiene diblock copolymer or hydrogenated product thereof, polystyrene-polybutadiene-polystyrene triblock copolymer or hydrogenated product thereof, polystyrene-polyisoprene diblock copolymer or hydrogenated product thereof, polystyrene-polyisoprene-polystyrene triblock copolymer or hydrogenated product thereof, and the like. These resins may be used alone or in combination of two or more. Among the above, thermoplastic resins are preferred from the viewpoint of improving the mechanical strength of the foamed sheet and the dispersibility of a heat absorbing agent, a heat storage material, and the like in the resin, which will be described later.

[0020] In addition, when the foamed sheet further contains a heat absorbing agent or a heat storage material described later, from the viewpoint of easily forming a structure having voids and easily ensuring the porosity, the resin is preferably an emulsion resin capable of forming voids by mechanical foaming. Examples of emulsion resins include acrylic emulsion resins, urethane emulsion resins, ethylene-vinyl acetate emulsion resins, vinyl chloride emulsion resins, and epoxy emulsion resins. Among them, acrylic emulsion resins are preferred because of their excellent heat resistance and heat insulation properties.

[0021] Examples of acrylic resins include resins obtained by polymerizing monomer components containing (meth)acrylic acid alkyl esters. In this specification, "(meth)acrylic" is a general term for acrylic, methacrylic, and both. "(meth)acrylate" is a general term for acrylate, methacrylate, and both. Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0022] In addition, the monomer component for obtaining the acrylic resin may contain a polar group-containing monomer in addition to the above-mentioned (meth)acrylic acid alkyl ester. Examples of the polar group-containing monomer include carboxylic acids having an ethylenically unsaturated group such as (meth)acrylic acid and itaconic acid; (meth)acrylates having a hydroxyl group such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone-modified (meth)acrylate, polyoxyethylene (meth)acrylate, and polyoxypropylene (meth)acrylate; and nitrogen-containing monomers having an ethylenically unsaturated group such as (meth)acrylonitrile, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinyllaurolactam, (meth)acryloylmorpholine, (meth)acrylamide, dimethyl (meth)acrylamide, N-methylol (meth)acrylamide, N-butoxymethyl (meth)acrylamide, and dimethylaminomethyl (meth)acrylate.

[0023] As the acrylic resin, polymethyl(meth)acrylate and polyethyl(meth)acrylate are preferable, polymethyl(meth)acrylate is more preferable, and polymethylmethacrylate (PMMA) is further preferable. The weight average molecular weight of the acrylic resin is preferably 1,000 to 100,000, more preferably 5,000 to 90,000, and even more preferably 20,000 to 80,000, from the viewpoints of easily improving the mechanical strength of the foamed sheet and easily dispersing a heat absorbing agent, a heat storage material, and the like in the foamed sheet. Here, the weight average molecular weight is a weight average molecular weight calculated in terms of standard polystyrene measured by gel permeation chromatography (GPC).

[0024] The average particle size of the emulsion resin is preferably 30 nm to 1500 nm, more preferably 50 to 1000 nm, from the viewpoint of easily coating the heat absorbing agent and favorably binding the heat absorbing agent coated with the resin. The average particle size of the emulsion resin can be the 50% median diameter measured by a dynamic light scattering method, for example, the 50% median diameter on a volume basis measured by a Microtrac UPA type particle size distribution measuring device manufactured by Nikkiso Co., Ltd.

[0025] The foamed sheet may be a foam of the above-mentioned resin, or may have a structure in which a heat absorbing agent and a heat storage material, which will be described later, are dispersed in the above-mentioned resin as a matrix, and have voids. In this case, the specific gravity of the foamed sheet is preferably 0.15 to 1.6, and more preferably 0.2 to 1.0. When the specific gravity of the foamed sheet constituting the secondary battery of the present invention is within the above range, the thermal insulation property can suppress the temperature effect between the battery cells, and the cushioning property acts as a buffer for the volume change caused by the expansion of the battery cells, and the internal pressure rise of the secondary battery is easily alleviated. Furthermore, the foamed sheet can be easily made lighter, and the processability is also good.

[0026] <Heat absorbing agent> Examples of the endothermic agent include inorganic hydrates, metal hydroxides, and carbonates, etc., which preferably have an endothermic peak at a temperature of 80° C. or higher. Specific examples include calcium sulfate dihydrate, magnesium sulfate heptahydrate, sodium hydrogen carbonate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, calcium carbonate, hydrotalcite, and zinc borate hydrate. Among them, at least one selected from the group consisting of calcium sulfate dihydrate, sodium hydrogen carbonate, aluminum hydroxide, magnesium hydroxide, and calcium carbonate is preferred, and at least one selected from the group consisting of calcium sulfate dihydrate, sodium hydrogen carbonate, and aluminum hydroxide is more preferred. The endothermic agent may be used alone or in combination of two or more types.

[0027] The endothermic starting temperature of the endothermic agent is preferably in the range of 60°C to 750°C, more preferably in the range of 80°C to 450°C, and further preferably in the range of 80°C to 300°C. The endothermic peak temperature of the endothermic agent is preferably in the range of 80°C to 800°C, more preferably in the range of 100°C to 500°C, and further preferably in the range of 100°C to 350°C. The endothermic amount of the endothermic agent is preferably in the range of 100 J / g to 1200 J / g, and more preferably in the range of 300 J / g to 1200 J / g. The endothermic onset temperature, endothermic peak temperature and endothermic amount of each endothermic agent were determined using a differential scanning calorimeter (DSC) according to the method described in the Examples below.

[0028] The foam sheet may contain one kind of heat absorbing agent alone, or may contain two or more kinds of heat absorbing agents. When two or more kinds of heat absorbing agents are contained, it is preferable to combine two or more kinds of heat absorbing agents having different endothermic onset temperatures or different endothermic peak temperatures. For example, when a heat absorbing agent (heat absorbing agent 1) having a relatively low endothermic onset temperature or endothermic peak temperature is mixed with a heat absorbing agent (heat absorbing agent 2) having a relatively high endothermic onset temperature or endothermic peak temperature, endothermic reactions are continuously generated during the temperature rise, and thermal runaway can be effectively suppressed. In addition, in secondary batteries, for example, the electrolyte often burns, and the electrolyte burns due to ignition or fire, but when two or more kinds of heat absorbing agents are contained, more effective fire extinguishing is possible by using an endothermic agent having an endothermic onset temperature corresponding to each of the flash point and ignition point. The endothermic onset temperatures of endothermic agent 1 and endothermic agent 2 preferably differ by 50° C. or more, more preferably by 100° C. or more. Alternatively, the endothermic peak temperatures of endothermic agent 1 and endothermic agent 2 preferably differ by 50° C. or more, more preferably by 100° C. or more. When two or more types of endothermic agents are contained, for example when endothermic agent 1 and endothermic agent 2 are contained, the mass ratio of the respective endothermic agents is not particularly limited, and the mass ratio of endothermic agent 1 / endothermic agent 2 can be appropriately set in the range of 10 / 90 to 90 / 10.

[0029] The particle size of the heat absorbing agent is preferably in the range of 1 μm to 100 μm, more preferably in the range of 1 μm to 80 μm. When the particle size of the heat absorbing agent is in the above range, the heat absorbing agent is easily dispersed uniformly in the foamed sheet, which is advantageous in terms of allowing a larger amount to be blended. The particle size of the endothermic agent is the median diameter (D50) value measured by a laser diffraction / scattering type particle size distribution measuring device.

[0030] When the foamed sheet contains an endothermic agent, the content thereof is preferably in the range of 10 mass % to 95 mass %, more preferably in the range of 50 mass % to 90 mass %, and further preferably in the range of 65 mass % to 90 mass %, based on the total components of the foamed sheet containing the endothermic agent and the resin as a matrix, from the viewpoint of easily realizing suitable endothermic properties. The content of the resin in the foamed sheet is preferably in the range of 5 to 90% by mass, more preferably in the range of 10 to 50% by mass, and even more preferably in the range of 10 to 35% by mass, from the viewpoint of easily adjusting the contents of the voids and the heat absorbing agent and easily increasing the contents of both. In addition, the ratio of the heat absorbing agent to the resin is preferably 80 / 20 to 15 / 85, more preferably 70 / 30 to 30 / 70, in terms of the solid content mass ratio represented by heat absorbing agent / resin, from the viewpoint of easily obtaining suitable heat retention and insulation properties.

[0031] <Heat storage material> The foamed sheet may further contain a heat storage material. The heat absorbing agent is a substance that decomposes by absorbing heat. In contrast, the heat storage material is positioned as a substance that absorbs heat when it changes phase from solid to liquid, and releases heat when it changes phase from liquid to solid. If a heat storage material with a relatively high temperature (i.e., melting point) at which the phase change occurs is selected, the heat storage material absorbs heat generated during charging of the secondary battery, thereby suppressing a sudden increase in temperature of the secondary battery, and preventing deterioration and ignition of the secondary battery. On the other hand, if a heat storage material with a relatively low temperature at which the phase change occurs is selected, when the temperature of the secondary battery decreases with a decrease in the ambient temperature, the heat storage material releases the heat stored therein, thereby preventing a decrease in temperature of the secondary battery. From the viewpoint of suppressing a sudden temperature rise of the secondary battery and better absorbing heat generated during charging, etc., the melting point of the heat storage material is preferably 15°C to 60°C, more preferably 20°C to 50°C, and even more preferably 30°C to 45°C.

[0032] The heat storage material is not particularly limited, but examples thereof include fatty acid esters, alkanes (paraffins), etc. These compounds may be used alone or in combination of two or more kinds. Examples of fatty acid esters include methyl myristate, methyl palmitate, ethyl palmitate, methyl stearate, ethyl stearate, etc. Among these, methyl palmitate, ethyl palmitate, methyl stearate, and ethyl stearate are preferred, and methyl stearate is more preferred. Examples of alkanes include hexadecane, heptadecane, octadecane, nonadecane, icosane, henicosane, docosane, etc. Among them, heptadecane, octadecane, nonadecane, icosane, henicosane, and docosane are preferred, nonadecane, icosane, henicosane, and docosane are more preferred, and icosane, henicosane, and docosane are even more preferred.

[0033] The heat storage material is preferably in the form of coated particles coated with an outer shell made of an organic material such as melamine resin, acrylic resin, or urethane resin. In this case, the average particle size of the coated particles is not particularly limited, but is preferably 10 μm to 3000 μm. By using coated particles having an average particle size in this range, it is easy to form voids between the coated particles in the foamed sheet, and it is easy to realize good moldability. The average particle size is more preferably 30 μm or more, even more preferably 50 μm or more, and particularly preferably 100 μm or more. In addition to forming suitable voids and having good moldability, the average particle size is more preferably 2000 μm or less, and even more preferably 1000 μm or less, from the viewpoint of easily retaining the coated particles in the foamed sheet. The average particle size of the primary particles is preferably within the above range. The average particle diameter of the coated particles can be measured using a laser diffraction particle size distribution measuring device (manufactured by Horiba, Ltd., "LA-950V2"), and the obtained median diameter (particle diameter equivalent to 50% of the volume cumulative distribution: 50% particle diameter) can be used.

[0034] Commercially available products may be used as such coated particles. For example, those having a shell made of melamine resin include Thermomemory FP-16, FP-25, FP-31, and FP-39 (all trade names) manufactured by Mitsubishi Paper Mills, and Riken Resin PMCD-15SP, 25SP, and 32SP (all trade names) manufactured by Miki Riken Kogyo Co., Ltd.; those having a shell made of silica include Riken Resin LA-15, LA-25, and LA-32 (all trade names) manufactured by Miki Riken Kogyo Co., Ltd.; those having a shell made of polymethyl methacrylate resin include Micronal DS5001X and 5040X (all trade names) manufactured by BASF; and those having a shell made of urethane resin include NJ2021 and NJ2721 (all trade names) of the "CALGRIP (registered trademark)" series manufactured by JSR Corporation.

[0035] <Other additives> The foam sheet may further contain other additives as required, such as flame retardants, adsorbents for harmful substances such as formaldehyde, deodorants, and coloring pigments. As the flame retardant, organic flame retardants and inorganic flame retardants can be appropriately used. The organic flame retardant is preferably, for example, a phosphorus compound, a halogen compound, or a guanidine compound. Specific examples of the organic flame retardant include primary ammonium phosphate, secondary ammonium phosphate, phosphoric acid triester, phosphorous acid ester, phosphonium salt, phosphoric acid triamide, chlorinated paraffin, ammonium bromide, decabromobisphenol, tetrabromobisphenol A, tetrabromoethane, decabromodiphenyl oxide, hexabromophenyl oxide, pentabromophenyl oxide, hexabromobenzene, guanidine hydrochloride, guanidine carbonate, and guanylurea phosphate. Examples of inorganic flame retardants include antimony and aluminum compounds, boron compounds, and ammonium compounds. Specific examples of such compounds include antimony pentoxide, antimony trioxide, sodium tetraborate decahydrate (borax), ammonium sulfate, and ammonium sulfamate. The flame retardants may be used alone or in combination of two or more.

[0036] <Physical properties of foam sheet> The thickness of the foamed sheet is preferably 100 μm to 20,000 μm, more preferably 100 μm to 6,000 μm, even more preferably 100 μm to 3,000 μm, and even more preferably 100 μm to 1,000 μm, which can further improve the cushioning properties, mechanical strength, and handleability such as processability of the foamed sheet.

[0037] The 25% compressive strength of the foamed sheet is preferably 10 kPa or more, more preferably 10 kPa to 1000 kPa, even more preferably 15 kPa to 700 kPa, and even more preferably 15 kPa to 600 kPa from the viewpoint of exhibiting good cushioning properties. Here, the 25% compression strength refers to a value obtained by measuring the strength when a foamed sheet cut into 30 mm square pieces with a thickness of approximately 1 mm is placed and compressed to approximately 0.25 mm (25% of the original thickness) at 23°C at a rate of 0.5 mm / min in accordance with JIS K 6767.

[0038] The mandrel diameter at which the foamed sheet cracks in a bending resistance test according to JIS K5600-5-1 (1999) is preferably 25 mm or less, more preferably 20 mm or less, and even more preferably 16 mm or less. A foamed sheet that satisfies such requirements can ensure suitable flexibility and excellent conformability to the surfaces of various members.

[0039] The tensile strength of the foamed sheet in the machine direction and the width direction is preferably 100 kPa or more, more preferably 200 kPa to 18,000 kPa. In this case, the foamed sheet can be made flexible yet strong. In addition, such a foamed sheet is less likely to crack during processing or transportation, and can exhibit suitable processability, handling properties, transportability, bending suitability, etc., which is preferable.

[0040] The tensile elongation at break in a tensile test of the foamed sheet is preferably 5% to 1500%, more preferably 30% to 1000%, further preferably 50% to 950%, and particularly preferably 60% to 800% in the machine direction. When the tensile modulus and tensile elongation of the foamed sheet are within the above ranges, excellent flexibility can be achieved while being tough, and the processability and workability in assembling the secondary battery of the present invention are good. The tensile strength of the foamed sheet in the machine direction and the width direction is the maximum strength measured by cutting the foamed sheet into a dumbbell shape using a Tensilon tensile tester in accordance with JIS K 6251 at a tension speed of 500 mm / min under conditions of 23°C and 50% RH.

[0041] Furthermore, it is preferable that the foamed sheet constituting the secondary battery of the present invention has a wide range of effective strain due to stress and a large compression ratio calculated from a stress-compression strain curve obtained in a compression test of the foamed sheet. With such a configuration, the expansion or contraction of the battery cell, for example in the stacking thickness direction, due to the deterioration of the secondary battery over time can be absorbed by the cushioning properties of the foamed sheet.

[0042] The average bubble diameter in the machine direction and width direction of the foamed sheet is preferably in the range of 10 μm to 500 μm, more preferably in the range of 30 μm to 400 μm, and even more preferably in the range of 50 μm to 300 μm. When the average bubble diameter in the machine direction and width direction of the foamed sheet is in the above range, the foamed sheet has excellent cushioning properties. In addition, the ratio of the average bubble diameter in the machine direction and width direction of the foamed sheet (average bubble diameter in the machine direction / average bubble diameter in the width direction) is preferably 0.2 to 4, more preferably 0.3 to 3, and even more preferably 0.4 to 1. When the ratio is in the above range, the flexibility and tensile strength of the foamed sheet in the machine direction and width direction are less likely to vary.

[0043] The average bubble diameter in the thickness direction of the foamed sheet is preferably in the range of 3 μm to 100 μm, more preferably in the range of 5 μm to 80 μm, and even more preferably in the range of 5 μm to 50 μm. The average bubble diameter in the thickness direction of the foamed sheet is preferably ½ or less, more preferably ⅓ or less, of the thickness of the foamed sheet. When the average bubble diameter in the thickness direction and the ratio to the thickness are within the above ranges, the foamed sheet has excellent cushioning properties, and is likely to achieve excellent adhesion to the case and the battery cell, and is likely to ensure the density and strength of the foamed sheet.

[0044] The foamed sheet preferably has a ratio of the average bubble diameter in its flow direction to the average bubble diameter in its thickness direction (average bubble diameter in its flow direction / average bubble diameter in its thickness direction) and a ratio of the average bubble diameter in its width direction to the average bubble diameter in its thickness direction (average bubble diameter in its width direction / average bubble diameter in its thickness direction) that are both at least 1, more preferably at least 3, and even more preferably from 4 to 25. When the foamed sheet has such an average bubble diameter ratio, the sheet has excellent flexibility in the thickness direction and is more excellent in adhesion to a case or a battery cell.

[0045] The average bubble diameter in the width direction, flow direction and thickness direction of the foamed sheet can be measured as follows. First, the foamed sheet is cut into pieces of 1 cm in the width direction and 1 cm in the flow direction. Next, a digital microscope (trade name "KH-7700", manufactured by HiROX) is set to a magnification of 200 times, and the cut surface of the foamed sheet in the width direction or flow direction is observed. At that time, the bubble diameters of all bubbles present within a range of 1.5 mm in the flow direction or width direction of the cut surface are measured. Next, the range of 1.5 mm is changed, and the bubble diameters of all bubbles present within any 10 ranges are measured. The average value of the bubble diameters measured above is calculated and the average bubble diameter is defined as the average bubble diameter.

[0046] The use of a foam sheet having a closed cell structure is preferred from the viewpoint of effectively preventing infiltration of water or dust from the cut surface of the foam sheet. The shape of the bubbles forming such a closed cell structure is preferably such that the average bubble diameter in the flow direction or width direction, or both directions, is larger than the average bubble diameter in the thickness direction, in order to obtain an appropriate cushioning property.

[0047] The apparent density of the foamed sheet is set to 0.08 g / cm because it is easy to adjust the compressive strength, average cell diameter, etc., within the above ranges and achieve both impact resistance and adhesion. 3 ~0.7g / cm 3 , preferably 0.1 g / cm 3 ~0.65g / cm 3 , more preferably 0.2 g / cm 3 ~0.65g / cm 3 , particularly preferably 0.3 g / cm 3 ~0.6g / cm 3 It is. The apparent density was measured according to JIS K 6767 by cutting a foam sheet into a 4 cm x 5 cm rectangle and measuring approximately 15 cm 3 The value was calculated by measuring the mass of each sample. The density, compressive strength, tensile strength, etc. of the foamed sheet can be appropriately adjusted depending on the material and foam structure of the foamed sheet.

[0048] <Method of manufacturing foam sheet> The foam sheet included in the secondary battery of the present invention can be produced by a method including mechanical foaming or chemical foaming. The foamed sheet can be produced by mechanically foaming the above-mentioned emulsion resin or a resin composition containing the above-mentioned emulsion resin and further a heat absorbing agent and a heat storage material, etc., followed by coating or casting and drying. When producing the foamed sheet, the resin composition may be dried and then cured by heat, ultraviolet light, etc., as necessary.

[0049] On the other hand, as a method for producing a foamed sheet by chemical foaming, the above-mentioned resin composition further containing a thermally decomposable foaming agent and a foaming assistant in the resin used as the material for the foamed sheet is fed to an extruder, melt-kneaded, extruded into a sheet to obtain a sheet, and then the thermally decomposable foaming agent in the sheet is foamed. Examples of the thermally decomposable foaming agent include azodicarbonamide, N,N'-dinitrosopentamethylenetetramine, p-toluenesulfonylsemicarbazide, etc., and one type may be used alone or two or more types may be used in combination. The amount of the thermally decomposable foaming agent added is usually preferably 1 part by mass to 40 parts by mass, more preferably 1 part by mass to 30 parts by mass, per 100 parts by mass of the resin, from the viewpoint of easily adjusting the expansion ratio, tensile strength, compression recovery rate, etc. to the desired range. In addition, the method for foaming the thermally decomposable foaming agent in the sheet is not particularly limited, and examples thereof include a method of heating with hot air, infrared rays, a salt bath, or an oil bath.

[0050] In the case where the foamed sheet further contains, for example, a heat absorbing agent, the content of the heat absorbing agent in the resin composition may be blended so that the mass ratio of the heat absorbing agent / resin in the foamed sheet is within the above-mentioned range, i.e., the solid content mass ratio represented by the heat absorbing agent / resin is preferably 80 / 20 to 15 / 85, more preferably 70 / 30 to 30 / 70. When preparing the foamed sheet, the resin composition may be mixed with a surfactant, a thickener, a flame retardant, a crosslinking agent, etc., if necessary. For example, in order to make the foam finer and stabilize the foamed bubbles, a surfactant can be mixed into the resin composition. As the surfactant, any of anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, etc. may be used. In particular, from the viewpoint of increasing the stability of the foamed foam, the surfactant is preferably an anionic surfactant, and more preferably a fatty acid ammonium surfactant such as ammonium stearate. The surfactant may be used alone or in combination of two or more kinds. When a surfactant is mixed into the resin composition, the content is preferably 30 parts by mass or less, more preferably 0.5 to 20 parts by mass, and even more preferably 3 to 15 parts by mass, per 100 parts by mass of the resin (solid content), since this makes it easier to obtain suitable foaming properties. A thickener can be mixed to improve the stability and film-forming properties of the foamed foam. Examples of the thickener include acrylic acid-based thickeners, urethane-based thickeners, and polyvinyl alcohol-based thickeners. Among them, acrylic acid-based thickeners and urethane-based thickeners are preferred. When a thickener is mixed into the resin composition, the content is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the resin (solid content).

[0051] In order to improve the mechanical strength of the foamed sheet, a curing agent may be mixed into the resin composition. The curing agent can be appropriately selected depending on the type of resin used, and examples of the curing agent include epoxy-based curing agents, melamine-based curing agents, isocyanate-based curing agents, carbodiimide-based curing agents, and oxazoline-based curing agents.

[0052] [Adhesive layer] From the viewpoint of further improving the adhesion between the battery cells in the secondary battery of the present invention, the foam sheet may be a laminate further having an adhesive layer on the outermost layers on both sides thereof, as shown in Fig. 3. That is, in the secondary battery of the present invention, the foam sheet may have an embodiment in which a plurality of battery cells are fixed by the adhesive layer further provided on the foam sheet. Examples of adhesives capable of forming an adhesive layer include those containing, as a binder, resins such as natural rubber, synthetic rubber, acrylic resins, silicone resins, urethane resins, vinyl ether resins, etc. The form of such adhesives may be any of solvent-based, emulsion-type, water-based, hot melt-type, and solventless types such as active energy ray-curable types such as ultraviolet rays and electron beams.

[0053] When the foam sheet has an adhesive layer on the outermost layer on both sides, the adhesive layers may have the same adhesive strength or different adhesive strengths. Specifically, one of the adhesive layers may be a so-called strong adhesive layer, and the other may be a weak adhesive layer. In addition, the adhesive layers may have the same composition or different compositions. The adhesive strength of the adhesive layer may be designed in consideration of the disassembly of the secondary battery. It is preferable that the adhesive capable of forming the adhesive layer contains a solvent from the viewpoint of maintaining good coating workability, etc. Examples of the solvent that can be used include toluene, xylene, ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, hexane, etc. In addition, when preparing a water-based adhesive composition, water or an aqueous solvent mainly composed of water can be used.

[0054] The adhesive capable of forming the adhesive layer may contain a tackifier resin, a crosslinking agent, other additives, and the like, as necessary. Examples of tackifying resins include various tackifying resins such as rosin-based, polymerized rosin-based, polymerized rosin ester-based, rosin phenol-based, stabilized rosin ester-based, disproportionated rosin ester-based, terpene-based, terpene phenol-based oils, and petroleum resin-based tackifying resins. Examples of crosslinking agents include known crosslinking agents such as isocyanate-based, epoxy-based, aziridine-based, polyvalent metal salt-based, metal chelate-based, ketohydrazide-based, oxazoline-based, carbodiimide-based, silane-based, and glycidyl (alkoxy) epoxy silane-based crosslinking agents, which can be used for the purpose of improving the cohesive strength of the adhesive layer. Other additives include known foaming agents, plasticizers, softeners, antioxidants, fillers such as glass or plastic fibers, balloons, beads, metal powders, etc., colorants such as pigments and dyes, pH adjusters, film-forming aids, leveling agents, thickeners, water repellents, defoamers, etc. These other additives can be added within a range that does not impair the desired effects of the present invention.

[0055] The thickness of the adhesive layer is preferably 10 μm or less, and more preferably in the range of 1 μm to 5 μm. The adhesive layer may contain the above-mentioned heat absorbing agent.

[0056] [Flame barrier layer] The foam sheet may be a laminate further having a flame-shielding layer. When the foam sheet has a flame-shielding layer, it can block the flame even if the secondary battery ignites due to sudden heat generation or temperature rise, and is effective in preventing or delaying the spread of fire to other battery cells. When the foam sheet further has both the adhesive layer and the flame-shielding layer, the flame-shielding layer is provided inside the adhesive layer. As the flame-proof layer, inorganic fiber sheets made of inorganic fiber woven fabric, nonwoven fabric, paper products, etc., and noncombustible paper can be suitably used. The flame-proof layer can be provided by laminating an inorganic fiber sheet on one surface of the foamed sheet, for example, as shown in FIG.

[0057] Specific examples of inorganic fiber sheets that can be used for the flame-shielding layer include glass cloth made of glass wool, rock wool, glass fiber, etc. The inorganic fiber sheets may be used alone or in combination of two or more kinds. From the viewpoint of exhibiting good flame-proofing properties, the thermal conductivity of the inorganic fiber sheet applicable to the flame-proofing layer is preferably 0.1 W / m K or less, and more preferably 0.05 W / m K or less. For example, the thermal conductivity of glass wool is about 0.045 W / m K. Specific examples of fireproof paper that can be used as a flame-shielding layer include paper that has been coated, impregnated, or internally added with a flame retardant to give it self-extinguishing properties and prevent the spread of flames. Examples of the flame retardant include metal oxides such as magnesium hydroxide and aluminum hydroxide, basic compounds such as phosphates, borates, and stephamates, and glass fibers. The thickness of the flame-shielding layer is not particularly limited and can be appropriately set within the range of, for example, 10 to 1000 μm. The weight per unit area of ​​the inorganic fiber sheet as the flame-shielding layer is 1 to 1000 mg / cm. 2 It is preferable that:

[0058] When the foam sheet is a laminate further comprising a layer of any other composition such as an adhesive layer, a flame-shielding layer, or an adhesive layer in addition to the layer containing the heat-absorbing agent and the resin as a matrix, there is no particular limitation on the method for producing such a laminate. For example, the laminate can be produced by a method of coating the above-mentioned adhesive on the surface of a release sheet, forming an adhesive layer by drying, etc., and transferring the adhesive layer to both surfaces of the foam sheet; a step of overlaying a flame-shielding layer on one surface of the foam sheet, if necessary via an adhesive layer, and transferring a pre-prepared adhesive layer to the other surface of the foam sheet and the surface of the flame-shielding layer; and a step of coating a resin containing a heat-absorbing material on the flame-shielding layer and heating to foam-mold. In addition, such a laminate can also be produced by directly coating and drying the above-mentioned adhesive on both surfaces of the foam sheet to form an adhesive layer. Examples of adhesives capable of forming the adhesive layer include urethane resin adhesives, acrylic resin adhesives, and polyester resin adhesives.

[0059] <Second embodiment> FIG. 2 is a partially cutaway perspective view showing a second embodiment of the secondary battery of the present invention. The secondary battery 100 of the second embodiment will be described below, focusing on the differences from the secondary battery 100 of the first embodiment, and a description of the similarities will be omitted. 2, a plurality of cylindrical battery cells 1 are arranged in a rectangular case 10. A foam sheet 20 is arranged on the inner surface of the case 10. The multiple battery cells 1 are stored (arranged) in the case 10 in a row and column (matrix) with the longitudinal direction (axial direction) being the thickness direction (height direction) of the case 10. In addition, a positive electrode terminal 12 for external connection collectively connected to the multiple positive electrode tabs 29 and a negative electrode terminal 13 for external connection collectively connected to the multiple negative electrode tabs 39 are provided on a side surface of the case 10.

[0060] Furthermore, a separator may be disposed inside the battery cell 1 and then wound. That is, a normal cylindrical battery cell may be used for each battery cell 1. In this case, the outer periphery of each battery cell 1 may be covered with the foamed sheet 30, or a plurality of battery cells 1 arranged in a row may be collectively covered with the foamed sheet 30. When using a foamed sheet 30 having a flame-shielding layer only on one side, it is preferable to dispose the foamed sheet 30 so that the surface of the flame-shielding layer faces the battery cell 1 (for example, so that the flame-shielding layer is in contact with the battery cell 1).

[0061] Although the secondary battery of the present invention has been described above, the present invention is not limited to the configuration of the above-mentioned embodiment. For example, the secondary battery of the present invention may have any other configuration added thereto for any purpose, or may be replaced with any configuration that exhibits a similar function, in the configuration of the above-mentioned embodiment. In addition, the foamed sheet 20 and the foamed sheet 30 may each be a laminate in which a plurality of sheets are laminated. EXAMPLES

[0062] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. The compounds used in the examples are shown below.

[0063] <Resin> Resin 1: "Boncoat 5400EF" (product name, water-dispersed acrylic resin emulsion, non-volatile content 50%, manufactured by DIC) Resin 2: "CN Paste 1805" (product name, vinyl chloride resin paste, manufactured by DIC Kitanihon Polymer) <Foam stabilizer> Foam stabilizer 1: "DICNAL M-40" (product name, sulfonic acid type anionic surfactant, manufactured by DIC) <Crosslinking agent> Crosslinking agent 1: "DICNAL GX" (product name, oxazoline group-containing polymer, manufactured by DIC) <Heat absorbing agent> Aluminum hydroxide: (product name "Aluminum hydroxide Grade 1", manufactured by Kanto Chemical) Calcium sulfate dihydrate: (product name "Calcium sulfate dihydrate Special grade", manufactured by Kanto Chemical) Sodium bicarbonate: (product name "Sodium bicarbonate Special grade", manufactured by Kanto Chemical)

[0064] 1. Examples of foam sheet manufacturing [Example 1] 100 parts by mass of resin 1 (water-dispersed acrylic resin emulsion), 6 parts by mass of foam stabilizer 1 (sulfonic acid type anionic surfactant), and 3 parts by mass of crosslinker 1 (oxazoline group-containing polymer) were mixed and stirred with a disperser (2000 rpm, 3 minutes) to prepare a mechanical foaming binder. The binder was stirred and foamed to double the foaming ratio, and stirring was continued for another 5 minutes to obtain a foamable mixture. The obtained foamable mixture was applied onto a polyethylene terephthalate (PET) film with an applicator, and then pre-dried at 105°C for 5 minutes, followed by heating at 120°C for 3 minutes. The film was then turned over and further heat-treated at 120°C for 3 minutes to harden it, producing a foamed sheet, Sheet 1, with a thickness of 1 mm. Sheet 1 has a specific gravity of 0.23 and a mass of 230 g / m 2 The cross section of the sheet 1 was examined using an electron microscope (Keyence Digital Microscope VHX-900).

[0065] [Example 2] 100 parts by mass of resin 1 (water-dispersed acrylic resin emulsion), 6 parts by mass of foam stabilizer 1 (sulfonic acid type anionic surfactant), and 3 parts by mass of crosslinker 1 (oxazoline group-containing polymer) were mixed and stirred with a disperser (2000 rpm, 3 minutes) to prepare a mechanical foaming binder. The binder was stirred and foamed to double the foaming ratio, and 240 parts by mass of aluminum hydroxide was mixed as a heat absorbing agent, and stirring was continued for another 5 minutes to obtain a foamable mixture. The obtained foamable mixture was applied onto a polyethylene terephthalate (PET) film with an applicator, and then pre-dried at 105°C for 5 minutes, heated at 120°C for 3 minutes, turned over, and further heat-treated at 120°C for 3 minutes to harden the film, producing a foamed sheet 2 with a thickness of 1 mm. Sheet 2 has a specific gravity of 0.64 and a mass of 640 g / m 2 , the mass of the heat absorbing agent in sheet 2 is 514 g / m 2The cross section of the sheet 2 was examined using an electron microscope (Keyence Digital Microscope VHX-900).

[0066] [Examples 3-4] Sheets 3 and 4 were produced as foam sheets in the same manner as in Example 2, except that the types and amounts of resin 1, foam stabilizer 1, crosslinking agent 1, and heat absorbing agent were as shown in Table 1. [Example 5] 100 parts by mass of resin 2 (vinyl chloride resin paste) was applied onto a PET film with an applicator, and then pre-dried by heating at 100°C for 5 minutes, and then cured by heat treatment at 140°C for 10 minutes to produce a sheet 5 having a thickness of 1 mm. [Example 6] A plastisol coating liquid was prepared by mixing 100 parts by mass of resin 2 (vinyl chloride resin paste) and 120 parts by mass of aluminum hydroxide as a heat absorbing agent. This plastisol coating liquid was applied to a PET film with an applicator, and then the film was heated at 100°C for 5 minutes as pre-drying, and then heat-treated at 140°C for 10 minutes to harden the film, producing a sheet 6 having a thickness of 1 mm.

[0067] [Example 1] The foamed sheet 1 obtained in Example 1 was used to fabricate a secondary battery of the first embodiment. [Examples 2 to 4] Using the foamed sheets 2 to 4 obtained in Examples 2 to 4, respectively, secondary battery modules were produced in the same manner as in Example 1. [Example 5] A laminate was obtained by laminating a glass cloth (thickness: 140 μm) via an adhesive layer on one surface of the foamed sheet 1 obtained in Example 1. The obtained laminate was sandwiched between battery cells to prepare a secondary battery module.

[0068] 2. Seat evaluation The 25% compression strength and the compression ratio at the effective strain end point were measured for each sheet obtained in Examples 1 to 6. The 25% compression strength was measured by measuring the strength when a foamed sheet cut into 30 mm squares and having a thickness of about 1 mm was placed and compressed to about 0.25 mm (25% of the original thickness) at a speed of 0.5 mm / min at 23°C according to JIS K 6767. In addition, the stress versus compression ratio was measured to obtain a stress-compression strain curve as shown in FIG. 5. Here, the inflection point at which the stress fluctuation range during compression begins to be ±10% was defined as the yield point, and the point at which the stress against compression begins to increase again was defined as the effective strain end point, and the compression ratio at the effective strain end point was obtained. The stress-compression strain curve of Example 1 specifically shows the yield point and the effective strain end point. The results are shown in Table 1. In particular, sheets 1 to 4 have a wide range of effective strain due to stress (from the yield point to the effective strain end point) and a large compression ratio at the effective strain end point, making them preferable as sheets capable of absorbing the expansion (in the thickness direction) of the battery cell of a secondary battery.

[0069] [Table 1] [Industrial Applicability]

[0070] The secondary battery of the present invention has a structure capable of absorbing the expansion and contraction that accompanies the deterioration over time of the battery cells that constitute the secondary battery, and is therefore useful for various applications as a secondary battery that ensures battery performance and battery life as well as improved battery safety. [Explanation of symbols]

[0071] 100 Secondary battery 1 Battery Cell 29 Positive tab 39 Negative tab 5 Sealing body 10 Cases 12 Positive terminal for external connection 13 Negative terminal for external connection 20 Foam Sheet 30 Foam Sheet 61 Foam Sheet 62 Adhesive layer 63 Flameproof layer

Claims

1. The battery pack includes two or more battery cells, a case for accommodating the battery cells, and either or both of a foam sheet disposed on the inner surface of the case and a foam sheet disposed so as to isolate adjacent battery cells from each other. The foamed sheet has a 25% compressive strength of 10 kPa or more, In the foamed sheet, a compressibility at an effective strain end point is 40% or more, when an inflection point at which the stress during compression starts to fluctuate within a range of ±10% in a stress-compression strain curve obtained by measuring the stress versus the compressibility is defined as a yield point, and a point at which the stress during compression starts to increase again is defined as an effective strain end point, The secondary battery, wherein the foam sheet contains at least one heat absorbing agent or heat storage material.

2. The secondary battery according to claim 1 , wherein the foam sheet further has an adhesive layer on the outermost layers on both sides, and the battery cell is fixed by the adhesive layer.

3. The secondary battery according to claim 1 or 2, wherein the foam sheet further comprises a flame-shielding layer.

4. A secondary battery as described in claim 1 or 2, wherein the foam sheet has a mass ratio of the heat absorbing agent to the resin of 80 / 20 to 15 / 85, expressed as a solid mass ratio of heat absorbing agent / resin.

5. 3 . The secondary battery according to claim 1 , wherein each of the battery cells is covered with the foam sheet in a state where a positive terminal and a negative terminal of each of the battery cells are exposed.

6. 3. The secondary battery according to claim 1, wherein the foam sheet has a thickness of 100 to 20,000 μm.

Citation Information

Patent Citations

  • Secondary battery device

    JP2013161681A

  • Thermally conductive foam materials

    JP2013514631A

  • Battery module

    JP2017162810A

  • Lithium-ion battery with thermal runaway protection

    JP2017524240A

  • Cushion material for battery

    JP2020139062A